Description of bilateral ideals in a class of noncommutative rings. I - Bavula, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For generalized Weil algebras of degree 1 with base Dedekind ring, bilateral ideals are classified. The (noncommutative) algebras, in which the product of ideals is permutable and any proper ideal is uniquely decomposed into the product of prime ideals, are described.